Legislation about utilization natural resources in Latin America (Revista Sistemas de Producción Agroecológicos, 2013)
During the past decade has significantly increased the attention of public and private organizations in relation to the environment, due to the implications that the deterioration and resource depletion have caused on stocks and sectors. To this extent, governments have generated a series of conditions for the use or exploitation of natural resources, regulating these provisions by laws, orders or decrees. It considers the environment as a common heritage and it is the duty of governments and individuals protect, and ensure the protection of the environment. Also considered are public goods, natural parks, communal lands of ethnic groups, land slip, and archaeological heritage, are inalienable and indefeasible. Therefore proposed Sustainable development actions to achieve economic growth, raising the quality of life and social welfare, without depleting the natural resource base that underpins renewable, or damaging the environment or the right to use future generations to satisfy their needs, therefore it is the duty of the state to plan the management and use of natural resources to ensure sustainable development, preservation or replacement. To comply with the provisions is required Environmental Impact Study (EIS), the set of information that must be submitted to the competent environmental authority the petitioner contain information on the location of the project, and elements abiotic, biotic and socioeconomic environment, which are subject to deterioration by the respective work or activity, the performance of which ask permission, and evaluation of impacts. Also include the design of plans for prevention, correction and compensation of impacts and the environmental management plan of the work or activity. Once the decision to implement the project is passed to the phase of collecting information about the project and the environment affected: In that vein, organizations are obliged to plan design and implement environmental management system, conceived as one that identifies significant aspects and impacts while proposes, implements and reviews actions aimed at the prevention, correction or mitigate these impacts.
Keywords: government laws; conservation; environment